Nano-encapsulated Iron and Folic Acid-Fortified Functional Yogurt Enhance Anemia in Albino Rats - Darwish, Amira M. G.; Soliman, Tarek N.; Elhendy, Hassan A.; El-Kholy, Wedad M. (Frontiers in Nutrition, 2021)
Iron deficiency anemia (IDA) is a major health concern in developing countries where increased incidence especially between pregnant women and children. The contribution of dairy products as natural products in drug delivery approaches is inspiring. This study aimed to the application of iron (Fe) and folic acid (FA) bovine serum albumin-nanoparticles (BSA-NPs) as anti-anemic pharmacological agents fortified in stirred functional yogurt (SFY) comparing with plain control and SFY fortified with Fe and FA in free forms. Physicochemical, cytotoxicity, microbiological, rheological, oxidative interactions, microstructural, sensorial analyses and the bioavailability in IDA induced Albino rats were examined. Transmission Electron Microscope (TEM), Zetasizer and Scan Electron Microscope (SEM) were applied. Nanocapsules fortified SFY showed enhanced apparent viscosity, water holding capacity, microstructure, the least lipid oxidation, and overall sensorial acceptability. Feeding Fe+FA nanocapsules fortified SFY (G6) succeeded to restore; hemoglobin (16.53 gdL-1), iron (109.25 μgdL-1), ferritin (33.25 μgdL-1) and total protein (8.6 gdL-1) at the end of the 4 weeks feeding period, with significant competition revealed in calcium and zinc absorbance. Nanocapsules fortified SFY showed no adverse effects or architectural alterations in liver, kidney, or spleen as biochemical or histological examinations indicated. Bovine serum albumin-nanoparticles (BSA-NPs) of iron (Fe) and folic acid (FA) can be recommended as anti-anemia supplement in different functional food applications.